Toward a holistic model of deception: subject matter expert validation - Reid, Iain D.; Black, Robert (University of Hawaii at Manoa, 2020)
Security challenges require greater insight and flexibility into the way deception can be identified and responded to. Deception research in interactions has identified behaviors indicative of truth-telling and deceit. Deception in military environments has focused on planning deception, where approaches have been developed to deceive others, but neglecting counter-deception perspectives. To address these challenges a holistic approach to deception is advocated. A literature review of deception was conducted followed by validation interviews with Subject Matter Experts (SMEs). Explanatory thematic analysis of interviews conducted with SMEs (n=19) led to the development of meta-themes related to the ‘deceiver’, their ‘intent; ‘strategies and tactics’ of deception, ‘interpretation’ by the target and ‘target’ decision-making strengths and vulnerabilities. This led to the development of the Holistic Model of Deception (HMD), an approach where strategies reflect context. The implications of this approach are considered alongside the limitations and future directions required to validate the HMD.
Keywords: Cyber Deception for Defense